2015
DOI: 10.1209/0295-5075/111/60013
|View full text |Cite
|
Sign up to set email alerts
|

Slowing-down of non-equilibrium concentration fluctuations in confinement

Abstract: Fluctuations in a fluid are strongly affected by the presence of a macroscopic gradient making them long-ranged and enhancing their amplitude. While small-scale fluctuations exhibit diffusive lifetimes, larger-scale fluctuations live shorter because of gravity, as theoretically and experimentally well-known. We explore here fluctuations of even larger size, comparable to the extent of the system in the direction of the gradient, and find experimental evidence of a dramatic slowing-down in their dynamics. We re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 38 publications
7
48
0
Order By: Relevance
“…A confirmation of this result has been obtained in a recent study on the effect of the confinement on the dynamics of nonequilibrium concentration fluctuations [17]. This study showed that the confinement effect starts to be felt at the reduced wave number qL = 5.18 = Ra 1/4 sc , where Ra sc = 720 is the critical solutal Rayleigh number.…”
Section: Root-mean-square Concentration Difference Between Two Pointssupporting
confidence: 76%
See 2 more Smart Citations
“…A confirmation of this result has been obtained in a recent study on the effect of the confinement on the dynamics of nonequilibrium concentration fluctuations [17]. This study showed that the confinement effect starts to be felt at the reduced wave number qL = 5.18 = Ra 1/4 sc , where Ra sc = 720 is the critical solutal Rayleigh number.…”
Section: Root-mean-square Concentration Difference Between Two Pointssupporting
confidence: 76%
“…An additional mechanism breaking the scale invariance of the fluctuations at small wave vectors was predicted theoretically to be the finite size of the sample [13], a finding confirmed experimentally during the GRADFLEX experiment by the European Space Agency [14][15][16]. Recent experiments showed that finite-size effects also affect the dynamics of the fluctuations in the presence of gravity [17]. The current understanding of nonequilibrium fluctuations is that they do not represent a mere perturbation of macroscopic nonequilibrium.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, for the rest of this paper we shall neglect the presence of boundaries. Previous studies show that confinement affects both the amplitude [25,26] and the dynamics [27] of NE fluctuations at lateral wave numbers q L −1 . Hence, our current results are expected to be valid only for fluctuations with q large enough, while we leave for future publications a thorough investigation of confinement effects on NE fluctuations in ternary mixtures.…”
Section: Fluctuating Hydrodynamicsmentioning
confidence: 97%
“…One other notable example of FHD success is the prediction of the influence of gravity on the fluctuations [23], an effect initially considered to be not accessible to experiments, and later confirmed by novel optical techniques [24]. Similarly, detailed FHD predictions about finite size effects on non-equilibrium fluctuations [25][26][27] have been later experimentally verified, by Gradflex [28] in microgravity and by ground-based measurements [27,29] in the presence of buoyancy force. Hence, as a preliminary step in developing the theory of thermodynamic fluctuations in NE ternary mixtures, it was necessary to re-derive [30] the equilibrium results for ternary mixtures on the basis of FHD, for which the simplifications of Bardow [4] were adopted.…”
Section: Introductionmentioning
confidence: 98%